The role of sialic acid in the immune response of patients with acute leukemia Almufaawi the subject and is on treatment Alkamiawi this - Baghdad Science Journal (مجلة بغداد للعلوم, 2005)
The focus of this research revolves around the importance level of sialic acid in the reasoning of cases, including tumors and then evaluate the patient's response to treatment and its impact on the immune response there are a lot of evidence showing that parts Alkrbu ???????? in peptides sugary and glycoproteins play an important role in Alfalitin life and responsiveness